2009
DOI: 10.1039/b820602c
|View full text |Cite
|
Sign up to set email alerts
|

Photoenhancement of lifetimes in CdSe/ZnS and CdTe quantum dot-dopamine conjugates

Abstract: The response of water-soluble, mercaptocarboxylic acid-capped fluorescent semiconductor nanoparticles, or quantum dots (QDs), to extended visible-light irradiation is variable and poorly described. Here we use time-resolved spectroscopy to investigate the photoluminescence intensities and lifetimes of CdSe/ZnS and CdTe QDs as a function of blue light illumination. Conjugates of the particles to the electron donor dopamine were also investigated, and the effect of the antioxidant beta-mercaptoethanol was explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…18, 24 Modification of a number of external environmental factors that influence the optical properties of QDs, such as the addition of electron donors and/or acceptors to the solution have been shown to affect fluorescence quenching, 17, 2528 blinking, 17, 2931 dark fraction 17 and fluorescence lifetime. 31, 32 Recent reports have shown that environmental factors can affect both the radiative and non-radiative rates simultaneously and unpredictably 31 which further complicates the interpretation. Additionally, the shell thickness and chemical composition of core-shell QDs have been shown to be important parameters that affect the optical properties.…”
mentioning
confidence: 99%
“…18, 24 Modification of a number of external environmental factors that influence the optical properties of QDs, such as the addition of electron donors and/or acceptors to the solution have been shown to affect fluorescence quenching, 17, 2528 blinking, 17, 2931 dark fraction 17 and fluorescence lifetime. 31, 32 Recent reports have shown that environmental factors can affect both the radiative and non-radiative rates simultaneously and unpredictably 31 which further complicates the interpretation. Additionally, the shell thickness and chemical composition of core-shell QDs have been shown to be important parameters that affect the optical properties.…”
mentioning
confidence: 99%
“…For instance, QD-dopamine bioconjugates stain dopamine-receptor-expressing cells in redox-sensitive patterns20. Dopamine as an electron donor could sensitize QDs through different mechanisms involving reactive oxygen species (ROS)20212223. Recently, we demonstrated that coupling QDs with cytochrome c is capable of fluorescence imaging of a superoxide radical with high specificity24.…”
mentioning
confidence: 99%
“…However conjugation of Pcs to CdSe@ZnS has not been reported. CdSe@ZnS QDs have been reported [27] to enhance fluorescence compared to CdTe@ZnS QDs, hence we study the former in this work. The conjugation of QDs to ClGaPc(COOH) 8 has to the best of our knowledge not been reported.…”
Section: Introductionmentioning
confidence: 97%